Investigation of the E-Selectin rs5368 (C468T) Single Nucleotide Polymorphism Role INA Group of Type Two Diabetes Mellitus Iraqi Patients - Nadia Fadhil Salman (Journal of Global Pharma Technology, 2018)
Introduction: E-select in his cell glycoprotein that is expressed on the surface of endothelial cells in response to proinflammatory cytokines and it supports the rolling of leukocytes at the sites of inflammation and tissue injury.  Diabetes mellitus is a global health problem represented by metabolic disorder in which the genetic predisposition and unhealthy lifestyle interact with environmental factors to unmask the disease which might be a result of inflammation reflecting response. Aim: Detection of the E- Selectin rs5368 (C468T) Single Nucleotide Polymorphism role in a group of Type 2 Diabetes Mellitus Iraqi patients.  Material and methods: The E- Selectin rs5368 (C468T) Single Nucleotide Polymorphism was characterized using Restriction Enzyme Fragment Length Polymorphism (RFLP-PCR) technique by designing new set of specific primers, then the PCR product was visualized by agarose gel electrophoresis. Results: There was no significant association found between any of the E-Selectin rs5368 (C468T) genotypes and the incidence of T2DM. Also there was no significant difference for the allele’s distribution between the patients and control groups. Conclusions:  This study showed a success in the primers design and the PCR- RFLP protocol and techniques for the E-Selectin rs5368 (C468T), the sequence of E-Selectin rs5368 (C468T) polymorphism is found to be in concordance with the global registered NCBI sequence. The genotyping results showed that the E-Selectin rs5368 (C468T) polymorphism is not associated with the incidence of T2DM. Also there was no significant difference for the allele’s distribution between the patients and control groups.Key words: Type 2 Diabetes Mellitus, E- Selectin rs5368 (C468T) Single Nucleotide Polymorphism.